Development of Interactive Teaching Materials in Port Operations and Facilities Courses - Dahri, M; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
This study aims to develop teaching materials for Port Operations and Facilities courses that are suitable for Sea Transportation DIV cadets at the Surabaya Shipping Polytechnic. This development follows the structured ADDIE Model. The resulting module aims to help students understand the subject material. Upon completion of designing the module, researchers gather feedback from subject matter experts and media experts, resulting in a highly valid module with no need for further revision. Recommendation: This module may require further improvement and assessment of effectiveness in the future. Development Limitations: The study had several limitations, including a focus on feedback from cadets and constraints related to time and resources.